Preparation method of sodium ion battery negative electrode material and sodium ion battery

By embedding phosphorus elemental material into the mesoporum of carbon material in the negative electrode material of sodium ion battery, the problem of volume expansion of phosphorus-based material during circulation is solved, and the cycle life performance of the battery is improved.

CN119742325APending Publication Date: 2025-04-01SOUTH CHINA UNIV OF TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411763197.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The energy density of sodium ion batteries is low, and the volume expansion of phosphorus-based materials during circulation, affecting the circulation performance.

Method used

By selecting mesoporous materials with suitable pore sizes, the vapor deposition method is used to embed the phosphorus elemental material in the mesoporous of carbon material, which restricts the expansion of the phosphorus material and ensures the contact and interface of the material during the circulation process.

Benefits of technology

The cycle life performance of sodium ion batteries is improved and the negative impact of the volume expansion of phosphorus-based materials on battery performance is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742325A_ABST
    Figure CN119742325A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a sodium ion battery negative electrode material and a sodium ion battery. The preparation method comprises the following steps: mixing a disordered mesoporous carbon material with red phosphorus, and carrying out sublimation, condensation and reaction in a vacuum environment or a protective atmosphere to obtain the sodium-ion battery negative electrode material. The average pore size of the disordered mesoporous carbon material is 2-20 nm. The sodium-ion battery negative electrode material is prepared by adopting a sublimation-condensation-reaction mode, so that a phosphorus material is fully deposited in mesopores of a carbon material and is finally converted into red phosphorus; and meanwhile, the average pore size of the disordered mesoporous carbon material is 2-20nm, so that the pore size is not large enough to embed excessive red phosphorus, and the problem that the cycle performance is seriously deteriorated due to serious expansion of the material in the cycle process is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a method for preparing a negative electrode material for a sodium ion battery and a sodium ion battery. Background Art

[0002] In recent years, new energy technologies have developed rapidly. In addition to the extremely high sodium content and extremely rich positive and negative electrode raw materials, sodium-ion batteries also have excellent rate performance, fast charging performance, low temperature performance, green environmental protection and high safety. They have become an important choice for low-speed vehicles, power vehicles and large-scale energy storage technologies. Therefore, they have recently received increasing attention from the scientific research and business communities.

[0003] Compared with lithium-ion batteries, the biggest disadvantage of sodium-ion batteries is their low energy density. Conventional negative electrode hard carbon materials are only about 300mAh / g, which is far lower than the 370mAh / g of graphite materials in lithium batteries. Therefore, the research on alloy negative electrode materials such as tin (about 800mAh / g) and phosphorus (about 2600mAh / g) has become an important direction for improving the energy density of sodium-ion batteries. However, like silicon materials in lithium-ion batteries, phosphorus-based materials also face the difficulty of volume expansion (about 400%) during the cycle, thereby affecting the cycle performance. The traditional method is to mix phosphorus materials with carbon materials and control the proportion of phosphorus in them to achieve the purpose of reducing volume expansion, but there is still a problem of poor cycle performance. Summary of the invention

[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a negative electrode material for a sodium ion battery and a sodium ion battery; the negative electrode material for a sodium ion battery prepared by the present invention not only maintains the high gram capacity characteristics of phosphorus-based materials, but also avoids the problem of volume expansion of phosphorus-based materials, thereby greatly improving the cycle life of sodium ion cylindrical batteries.

[0005] The present invention selects mesoporous materials with suitable pore sizes and uses a vapor deposition method to embed phosphorus materials in the mesopores of carbon materials. The mesoporous materials can restrain the expansion of the phosphorus materials during the charge and discharge cycle, thereby ensuring that the contact and interface conditions between the various materials in the electrode during the cycle will not be damaged due to the stress generated by the material expansion, thereby ensuring the battery cycle life performance.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] The present invention provides a method for preparing a negative electrode material for a sodium ion battery, comprising the following steps:

[0008] After the disordered mesoporous carbon material is mixed with red phosphorus, sublimation, condensation and reaction are performed in a vacuum environment or a protective atmosphere to obtain a negative electrode material for a sodium ion battery;

[0009] The average pore size of the disordered mesoporous carbon material is 2-20 nm.

[0010] Preferably, the average pore diameter of the disordered mesoporous carbon material is 4-15 nm.

[0011] Further preferably, the average pore diameter of the disordered mesoporous carbon material is 4.8-10 nm.

[0012] Preferably, the mass ratio of the disordered mesoporous carbon material to red phosphorus is 3:7 to 7:3;

[0013] Preferably, the average particle size of the disordered mesoporous carbon material is 0.5-10 microns, and the specific surface area is 200-800 m 2 / g.

[0014] Further preferably, the average particle size of the disordered mesoporous carbon material is 1-5 microns.

[0015] Preferably, the mixing is stirring mixing or ball milling mixing;

[0016] Preferably, the average particle size of the red phosphorus is 5-50 nm; and the purity of the red phosphorus is greater than or equal to 97%.

[0017] Preferably, the protective atmosphere is argon, helium or nitrogen.

[0018] Preferably, the sublimation insulation temperature is 450-500°C, the sublimation insulation time is 3-5 hours, and the sublimation heating rate is 3-4°C / min;

[0019] Preferably, the cooling rate of the condensation is 0.5-1°C / min, and the termination temperature of the condensation is 260-270°C;

[0020] Preferably, the insulation temperature of the reaction is 260-270° C., and the insulation time of the reaction is 10-15 hours.

[0021] Preferably, after the reaction is completed, the reaction is naturally cooled to room temperature, washed, and dried;

[0022] More preferably, washing is performed by rinsing with carbon disulfide, benzene or ether; and drying is performed in a vacuum environment at 60-80°C.

[0023] The present invention provides a negative electrode material for a sodium ion battery prepared by the above preparation method.

[0024] The present invention provides the use of the above-mentioned sodium ion battery negative electrode material in the preparation of a sodium ion battery.

[0025] The present invention provides a sodium ion battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte; the negative electrode sheet comprises the above-mentioned sodium ion battery negative electrode material.

[0026] Preferably, the negative electrode plate also includes hard carbon, and the mass ratio of the hard carbon to the sodium ion battery negative electrode material is 50:50 to 99:1.

[0027] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows:

[0028] The present invention adopts a sublimation-condensation-reaction method to prepare the negative electrode material of the sodium ion battery, so that the phosphorus material is fully deposited in the mesopores of the carbon material and finally converted into red phosphorus.

[0029] The average pore size of the disordered mesoporous carbon material used in the present invention is between 2 and 20 nm, ensuring that the pore size is not large enough to embed excessive red phosphorus, thereby avoiding severe expansion of the material during the cycle process and ultimately causing severe deterioration of the cycle performance.

[0030] The average particle size of the disordered mesoporous carbon material used in the present invention is between 0.5 and 10 microns, and the specific surface area is between 200 and 800 m 2 / g, ensuring that enough phosphorus can be embedded in the mesopores during the sublimation-condensation process, so that the final red phosphorus carbon material has a higher capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is the first cycle charge and discharge curve of the button cell (half-charged) prepared from the phosphorus-carbon composite in Example 1.

[0032] Figure 2 The 21700 cylindrical sodium ion battery cycle performance diagram of Example 1 and Comparative Examples 1-2.

[0033] Figure 3 These are pictures of the positive and negative electrode sheets of the 21700 cylindrical sodium-ion batteries of Example 1 and Comparative Examples 1-2 disassembled after the first cycle of charge and discharge (the red arrow indicates the negative electrode sheet).

[0034] Figure 4 This is a picture of the positive and negative electrode sheets of the 21700 cylindrical sodium-ion battery of Comparative Example 1 after 500 cycles (the red arrow indicates the breakage of the electrode sheet). DETAILED DESCRIPTION

[0035] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. If the manufacturer of the reagents or instruments used is not indicated, they are deemed to be conventional products that can be purchased commercially.

[0036] Embodiment 1:

[0037] A method for preparing a sodium ion battery negative electrode material and a sodium ion battery, comprising the following steps:

[0038] (1) Preparation of negative electrode materials for sodium ion batteries

[0039] The disordered mesoporous carbon material and red phosphorus are stirred and mixed to obtain a phosphorus-carbon mixture, wherein the mass ratio of the disordered mesoporous carbon material to the red phosphorus is 5:5. The average particle size of the disordered mesoporous carbon material is 1 micron, and the specific surface area is 350 mm 2 / g, and the average pore size is 4.8nm; the average particle size of the red phosphorus is 6nm, and the purity is 97%.

[0040] Then, the phosphorus-carbon mixture is placed in a vacuum sealed container to obtain a phosphorus-carbon composite (i.e., a negative electrode material for a sodium ion battery) by a sublimation-condensation-reaction method, and the specific method is as follows:

[0041] The phosphorus-carbon mixture is placed in a vacuum-sealed stainless steel container, heated to 450°C at a heating rate of about 4°C / min and maintained for 3 hours, and then cooled to 270°C at a rate of 1°C / min, so that the red phosphorus sublimates (in the white phosphorus state) and condenses into the pores of the disordered mesoporous carbon material, and the temperature is maintained for 10 hours to ensure that all white phosphorus is completely converted into red phosphorus, and then naturally cooled to room temperature. The final composite is rinsed with carbon disulfide and dried in a vacuum environment at 60°C to obtain a phosphorus-carbon composite.

[0042] (2) Preparation of sodium ion batteries

[0043] Preparation of positive electrode

[0044] By mass, the O3 phase layered metal oxide (NaCu 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 O2), conductive carbon material (carbon black SP) and polyvinylidene fluoride glue (5wt%) are mixed together in a mass ratio of 95:3:2, stirred at 3000rpm in a vacuum stirring tank for 2h to obtain slurry, and then the slurry is evenly coated on both sides of an aluminum foil with a thickness of 15μm, and then dried (the total thickness after drying is about 160μm), rolled and cut into pieces to prepare a positive electrode sheet.

[0045] Preparation of negative electrode

[0046] 94wt% of the total mass of hard carbon material and the above-mentioned phosphorus-carbon composite (the ratio of hard carbon to phosphorus-carbon composite is 90:10) and 3wt% of conductive carbon material (carbon black SP) are stirred and mixed in a vacuum stirring tank at 1000rpm for 30min, and then 1.5wt% of sodium carboxymethyl cellulose emulsion (2.0wt%) is added and stirred at 1500rpm for 2h, and finally 1.5wt% of styrene-butadiene rubber emulsion (40% solid content) is added and stirred at 800rpm for 1h. Then the prepared slurry is evenly coated on both sides of aluminum foil with a thickness of 15μm, dried (the total thickness after drying is about 200μm), rolled, and the maximum compaction density of the electrode is tested, and finally cut into negative electrode sheets.

[0047] Preparation of sodium ion batteries

[0048] The dry electrode is wound in the order of positive electrode / diaphragm / negative electrode / diaphragm, and then put into the shell and spot welded, and a 1 mol / L sodium hexafluorophosphate electrolyte is prepared. The solvent is EC (ethylene carbonate), EMC (ethyl methyl carbonate) and PC (propylene carbonate), the additive is FEC, and the mass ratio of the solvent to the additive is EC:EMC:PC:FEC=16:40:40:4. After conventional processes such as liquid injection and composition (using constant current 0.2C), a 21700 cylindrical sodium ion battery is prepared.

[0049] Embodiment 2:

[0050] The disordered mesoporous carbon material is replaced with a specific surface area of ​​250mm 2 / g, the material has an average pore diameter of 10nm, and the rest is the same as Example 1.

[0051] Embodiment 3:

[0052] The disordered mesoporous carbon material is replaced with a material with an average particle size of 5 μm, and the rest is the same as in Example 1.

[0053] Embodiment 4:

[0054] The final temperature of the phosphorus-carbon mixture was changed to 500° C., and the rest was the same as in Example 1.

[0055] Comparative Example 1:

[0056] The average pore diameter of the disordered mesoporous carbon material is 150 nm, and the rest is the same as in Example 1.

[0057] Comparative Example 2:

[0058] (1) Preparation of negative electrode materials (phosphorus-carbon mixture) for sodium ion batteries

[0059] The disordered mesoporous carbon material and red phosphorus are stirred and mixed to obtain a phosphorus-carbon mixture, wherein the mass ratio of the disordered mesoporous carbon material to the red phosphorus is 5:5. The average particle size of the disordered mesoporous carbon material is 1 micron, and the specific surface area is 350 mm 2 / g, and the average pore size is 4.8nm; the average particle size of the red phosphorus is 6nm, and the purity is 97%.

[0060] The phosphorus-carbon mixture is directly used to prepare the negative electrode plate without undergoing the sublimation-condensation-reaction in Example 1, and step (2) is the same as in Example 1.

[0061] Performance Test:

[0062] (1) After mixing hard carbon and phosphorus-carbon composite in a mass ratio of 9:1, the negative electrode sheet (coated on one side) was made according to the conventional electrode production process, and then used as a counter electrode with the sodium sheet to make a standard 2025 model. The charge and discharge current was 0.1C at 0-1.5V. The first cycle charge and discharge data were obtained as follows Figure 1 shown.

[0063] from Figure 1 It can be seen that the first cycle sodium insertion capacity of the negative electrode material is 461.3mAh / g, the sodium removal capacity (reversible capacity) is 393.8mAh / g, and the first efficiency is 85.4%. According to the reversible capacity of hard carbon of 300mAh / g, the reversible capacity of the phosphorus-carbon composite is about 1238mAh / g. According to the ratio of phosphorus: carbon in the phosphorus-carbon composite of 50:50, the reversible capacity of phosphorus is about 2476mAh / g, which is very close to the theoretical value of phosphorus 2600mAh / g.

[0064] (2) The coated and dried negative electrode sheet was rolled by a rolling machine. After 1 day (before winding), the expansion rate and maximum compaction density of the electrode sheet are shown in Table 1;

[0065] After the 21700 cylindrical sodium ion battery was filled and sealed, it was placed for 48 hours, then charged to 3.95V with 0.2C constant current and constant voltage, then discharged to 1.5V with 0.2C constant current, and finally charged to 3.95V with 0.2C constant current and constant voltage. At this time, the expansion rate of the negative electrode sheet was measured after the battery was disassembled, as shown in Table 1, and the first cycle discharge capacity and first efficiency were shown in Table 1;

[0066] After the 21700 cylindrical sodium ion battery after 0.2C charge-discharge-charge was stored at 60°C for 7 days, the capacity of 0.2C constant current discharge was divided by the original capacity to obtain the capacity retention rate, and then the capacity was charged to 3.95V with 0.2C constant current constant voltage and then discharged to 1.5V with 0.2C constant current and divided by the original capacity to obtain the capacity recovery rate. The capacity retention rate at 60°C for 7 days and the capacity recovery rate at 60°C for 7 days are shown in Table 1;

[0067] The 21700 cylindrical sodium ion battery after 0.2C charge-discharge-charge was run with 0.5C constant current constant voltage charge (3.95V) / 1C constant current discharge (1.5V) to run the cycle data. The data are shown in Table 1 and Figure 2 .

[0068] Table 1 Performance comparison of negative electrode sheets and 21700 cylindrical sodium ion batteries of various embodiments and comparative examples

[0069]

[0070] It can be seen from Table 1 that the expansion rate of the negative electrode sheet of the battery of Examples 1-4 is low after full charge, and the cycle stability is good. The expansion rate of the negative electrode sheet of the battery in Comparative Example 1 is relatively high after full charge, which may be due to the fact that the pores of the porous carbon are too large, the size of the embedded phosphorus element is too large, and the volume expansion after sodium embedding exceeds the capacity of the carbon pores to bind, resulting in excessive volume expansion. The expansion rate of the negative electrode sheet of the battery in Comparative Example 2 is very high after full charge, and the reason is similar to that of Comparative Example 1, except that the phosphorus is not effectively embedded in the carbon pores, so the volume expansion of phosphorus is not bound by any carbon pores.

[0071] from Figure 2 It can be seen that the cycle performance of Comparative Example 1 deteriorates rapidly after 300 cycles. The reason should be that the phosphorus embedded in the porous carbon pores agglomerates into large particles. The sodium in the cycle process is deintercalated in the phosphorus for a long time, which will cause a dramatic volume expansion until the carbon pores collapse at a certain moment, exposing a large number of fresh interfaces to react with the electrolyte, consuming a large amount of active sodium in the system, and finally causing the cycle performance to deteriorate rapidly. The porous carbon and phosphorus in Comparative Example 2 are simply mechanically mixed. After the first cycle of charge and discharge, the porous carbon will inevitably consume more active sodium, resulting in the low first efficiency phenomenon in Table 1. In addition, the volume expansion problem of phosphorus during the cycle also causes its poor cycle performance.

[0072] The 21700 cylindrical sodium ion batteries prepared in Example 1 and Comparative Examples 1-2 were disassembled after the first cycle of charge and discharge. The positive electrode sheets and negative electrode sheets after the first cycle of charge and discharge were as follows: Figure 3 Figure 3 shown.

[0073] from Figure 3 It can be seen that the negative electrode sheet produced in Example 1 has fewer wrinkles after the first cycle of charge and discharge, has better flexibility, and can better meet the performance requirements of cylindrical batteries.

[0074] The 21700 cylindrical sodium ion battery prepared in Comparative Example 1 was disassembled after 500 cycles. The positive electrode sheet and the negative electrode sheet after 500 cycles were as follows: Figure 4 Figure 4 shown.

[0075] from Figure 4It can be seen that the phosphorus in the negative electrode sheet of the 21700 cylindrical sodium ion battery in Comparative Example 1 squeezes the internal electrode sheet after the volume expands to a certain extent, resulting in stress concentration, breakage of the positive and negative electrode sheets, and rapid deterioration of the battery cycle performance.

[0076] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention shall be equivalent replacement modes and shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a negative electrode material for a sodium ion battery, characterized in that: The following steps are involved: After the disordered mesoporous carbon material is mixed with red phosphorus, sublimation, condensation and reaction are performed in a vacuum environment or a protective atmosphere to obtain a negative electrode material for a sodium ion battery; The average pore size of the disordered mesoporous carbon material is 2-20 nm.

2. The method for preparing a negative electrode material for a sodium ion battery according to claim 1, characterized in that: The mass ratio of the disordered mesoporous carbon material to red phosphorus is 3:7 to 7:3; The average particle size of the disordered mesoporous carbon material is 0.5-10 microns, and the specific surface area is 200-800m 2 / g.

3. The method for preparing a negative electrode material for a sodium ion battery according to claim 1, characterized in that: The mixing is stirring mixing or ball milling mixing; The average particle size of the red phosphorus is 5-50nm; the purity of the red phosphorus is greater than or equal to 97%.

4. The method for preparing a negative electrode material for a sodium ion battery according to claim 1, characterized in that: The protective atmosphere is argon, helium or nitrogen.

5. The method for preparing a negative electrode material for a sodium ion battery according to claim 1, characterized in that: The sublimation insulation temperature is 450-500°C, the sublimation insulation time is 3-5 hours, and the sublimation heating rate is 3-4°C / min; The cooling rate of the condensation is 0.5-1°C / min, and the termination temperature of the condensation is 260-270°C; The insulation temperature of the reaction is 260-270° C., and the insulation time of the reaction is 10-15 hours.

6. The method for preparing a negative electrode material for a sodium ion battery according to claim 1, characterized in that: After the reaction is completed, the mixture is naturally cooled to room temperature, washed, and dried; Wash with carbon disulfide, benzene or ether; dry in a vacuum environment at 60-80℃.

7. A sodium ion battery negative electrode material prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the sodium ion battery negative electrode material according to claim 7 in the preparation of sodium ion batteries.

9. A sodium ion battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet and an electrolyte; the negative electrode sheet comprises the sodium ion battery negative electrode material according to claim 7.

10. The sodium ion battery according to claim 9, characterized in that: The negative electrode plate also includes hard carbon, and the mass ratio of the hard carbon to the sodium ion battery negative electrode material is 50:50 to 99:1.

Citation Information

Patent Citations

  • Thousand-layer bark biomass carbon loaded red phosphorus sodium ion battery anode material and preparation method thereof

    CN109286002A

  • Self-supporting phosphorus / carbon three-dimensional conductive network composite electrode material and preparation method and application thereof

    CN113363452A

  • Composite black phosphorus-based phosphorus-carbon negative electrode material and preparation method thereof

    CN117691059A

  • Preparation method and application of phosphorus-coated porous carbon composite material

    CN118472214A

  • Porous silicon / carbon and high-capacity silicon / phosphorus / carbon composite lithium battery negative electrode material and preparation method thereof

    CN118833802A